Pengaruh Stress Kerja dan Kompensasi Terhadap Kepuasan Kerja Pada Dinas Pendidikan Kota Medan - Ilyas Hadi Pane; Salman Farisi (Fisarrearch, 2020)
This study aims to determine the effect of job stress and compensation on job satisfaction at the Medan City Education Office. This research is a quantitative study using questionnaire data collection techniques. The population in this study amounted to 108 employees and the sample taken was 85 employees of the Medan City Education Office. The sampling technique used was purposive sampling technique. The analytical method used is multiple linear regression analysis. The results showed that the value of Job Stress T = 6.187 then obtained Tcount>Ttable or 6.187>1,663, a significant value of 0.000 T table or 4.808>1,663, a significant value of 0.000 Ftable or 67.567>2,716, a significant value of 0.000